(untitled) (Journal of Health Informatics in Africa, 2013)
Background and Purpose: Varying interests and expectations of different stakeholders have implications on successful implementation of Information and Communication Technologies for Health (ICT4H) interventions. Research has shown that proper management of stakeholders’ interests has a positive bearing on the effectiveness and sustainability of Information and Communication Technologies for Development (ICT4D) initiatives. However, there is a dearth of studies on stakeholder management in ICT4H research, especially the mobile for health (mHealth) domain. This could be due to the mHealth field still being in its infancy and many projects being implemented for a short period without being evaluated. This paper reports on management of stakeholders in an mHealth intervention from the community perspective. The study examined how management of stakeholders from the community affected the effectiveness and sustainability of the mHealth intervention. Methods: The case of a Mobile System for Safe Motherhood intervention in maternal health in a developing country context was analysed. The study employed an interpretive approach using qualitative methods. Documentary review and semi-structured interviews were used to collect data, and the data was analysed using content analysis. Results: Different expectations of mothers and other community agents were not given adequate voice and attention in reaching the common good towards achieving the main objectives of the intervention. Stakeholder management from the community perspective was inadequate due to: 1) less consultation of key community stakeholders in some stages of the project; 2) poor communication; 3) lack of formal procedures in operations; and 4) exclusion of tradition information systems. Conclusions: Management procedures such as face to face meetings, training, effective communication using formal channels, and community empowerment would help in building winning coalitions that improve performance of interventions and enhance effectiveness and sustainability. Keywords: mHealth, Community involvement, Stakeholder management